2010
DOI: 10.1097/mpa.0b013e3181bab5c5
|View full text |Cite
|
Sign up to set email alerts
|

Role of High-Mobility Group Box 1 Protein in the Pathogenesis of Intestinal Barrier Injury in Rats With Severe Acute Pancreatitis

Abstract: Our results demonstrate that HMGB1 participates in intestinal barrier injury in SAP and EP might play a therapeutic role in intestinal inflammation in this SAP model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…HMGB1 is one of the pro-inflammatory cytokines during acute lung injury. Our previous study demonstrated that blocking HMGB1 rescues barrier function and inhibits inflammation response of endothelial cells [15-17]. In this study, we further investigated its underlying mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…HMGB1 is one of the pro-inflammatory cytokines during acute lung injury. Our previous study demonstrated that blocking HMGB1 rescues barrier function and inhibits inflammation response of endothelial cells [15-17]. In this study, we further investigated its underlying mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…In the gastrointestinal tract, increased levels of HMGB1 have positively correlated with intestinal barrier dysfunction and colonic inflammation in mice (Dave et al, 2009; Liu et al, 2006; Luan et al, 2010; Maeda et al, 2007; Sappington et al, 2002; Wu et al, 2009; Yang et al, 2009a). Moreover, fecal HMGB1 is a novel biomarker of intestinal mucosal inflammation in patients with inflammatory bowel disease (Vitali et al, 2011), whereas serum HMGB1 is diagnostic marker in patients with acute appendicitis (Albayrak et al, 2011; Soreide, 2011; Wu et al, 2012a).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…The circulating inflammatory cytokines including TNF- α , IL-6, and HMGB1 also contribute to gut mucosal injury [2932], among these inflammatory cytokines, extracellular HMGB1 triggers and sustains the inflammatory response by inducing cytokine release and by recruiting leucocytes [33]. However, HMGB1 undergoes extensive posttranslational modifications, in particular acetylation and oxidation, which significantly modulate the functions of HMGB1 [33, 34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to identify the key factor that mediates intestinal BT in SAP. Gut bacteria can adhere to the injured intestinal mucosa that is necessary but not sufficient to induce gut BT in which HMGB1 and other unknown factors are also needed, because evidence shows that exogenous HMGB1 injection can induce gut mucosal injury and evident BT in normal mice [29], and HMGB1 also contributes to gut barrier dysfunction in rats with SAP [32]; blockade of HMGB1 reduces 85% of BT but does not significantly improve gut mucosal injury during acetaminophen hepatotoxicity [19]; similarly, ethyl pyruvate (EP), which is a HMGB1 inhibitor [39], reduces 80% of the gut BT but did not significantly decrease intestinal mucosal hyperpermeability in a lethal SAP animal model [6]; this BT-inhibition effect is associated with EP inhibiting 80% of the hepatic tissue HMGB1 release [15]. These evidences indicate that HMGB1 might mediate gut BT in SAP, and this hypothesis is confirmed by the following experiment: neutralization of HMGB1 decreased 70% of the gut BT (4252 ± 205 CFU/g for the sham antibody group versus 1235 ± 41 CFU/g for the anti-HMGB1 group, results are mean ± SEM, n = 6 for each group, unpublished data) but did not reduce gut mucosal hyperpermeability in another commonly used murine SAP model (7 hourly 50  μ g/kg intraperitoneal injections of cerulean and a single intraperitoneal injection of 4 mg/kg Escherichia coli lipopolysaccharide).…”
Section: Introductionmentioning
confidence: 99%